The answer is
x=2t and t=x/2, but we have <span>y = 3t -1
so </span><span>y = 3(x/2) -1
so y = 3x/2 - 1</span>
When subtracting fractions, you need to make sure the denominators are the same. In 2/3 - 1/2, the denominators are different. To make them the same, find the least common denominator. In this case, the common denominator is 6
2/3 becomes 4/6
1/2 becomes 3/6
Now subtract the fractions with the common denominator
4/6 - 3/6 = 1/6
The answer is 1/6
Hope this helps. Please mark me as Brainliest. Thanks!
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
y-(12*x^2-9*x+4)=0
Step by step solution :<span>Step 1 :</span><span>Equation at the end of step 1 :</span><span> y - (((22•3x2) - 9x) + 4) = 0
</span><span>Step 2 :</span><span>Equation at the end of step 2 :</span><span> y - 12x2 + 9x - 4 = 0
</span><span>Step 3 :</span>Solving a Single Variable Equation :
<span> 3.1 </span> Solve <span> <span>y-12x2+9x-4</span> </span> = 0
In this type of equations, having more than one variable (unknown), you have to specify for which variable you want the equation solved.
Answer:
12
Step-by-step explanation:
Factors of 30: 1,2,3,5,(6),10,15,30
Factors of 42: 1,2,3,(6),7,14,21,42
30 divided by 6, 42 divided by 6
(5) + (7)= 12
Bsuskshdjskshsosshdkshsksbxksmsjs